2000
DOI: 10.1046/j.1365-2672.2000.01056.x
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Lactobacillus plantarum isolates from Feta cheese throughout ripening

Abstract: Thirty‐two Lactobacillus plantarum strains isolated from Feta cheese throughout ripening were studied for their phenotypic characteristics, protein profile of cell‐free extracts, enzyme profiles, plasmid profiles, proteolytic and acidifying abilities and ability to grow at low pH and in the presence of bile. Results showed that some biotechnologically important characteristics, such as acidifying and proteolytic activities, can differ between strains. In addition, different plasmid profiles suggest the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 18 publications
1
30
0
3
Order By: Relevance
“…In contrast, the acidifying rate of isolates after 24 h of incubation was lower than those reported in the former studies. The possibility to find groups of strains characterized by different acidifying ability is frequent in L. plantarum species (49). …”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the acidifying rate of isolates after 24 h of incubation was lower than those reported in the former studies. The possibility to find groups of strains characterized by different acidifying ability is frequent in L. plantarum species (49). …”
Section: Resultsmentioning
confidence: 99%
“…The Lactobacillus paracasei DC205 and DC412 12 and Saccharomyces boulardii KK1 13 strains were obtained from the collection of the Laboratory of Food Microbiology and Hygiene of Aristotle University of Thessaloniki-Greece. All lactobacilli were stored at À801C in MRS broth with 25% glycerol, and KK1 cultures were maintained at 41C in a YEGP agar slope.…”
Section: Bacterial Strains and Growth Conditionsmentioning
confidence: 99%
“…Our results were in accordance with those of Ruiz-Barba et al (1991) who showed that 35 L. plantarum strains, isolated from different green olive fermentors, contained a large number of plasmids in the CCC form (from 5 to 16) ranging from 2.0 to 68 kb in size. Xanthopoulos et al (2000) also have found different plasmids in several L. plantarum strains isolated from Feta cheese. Delgado and Mayo (2003) have reported that L. plantarum LL441 strain harbours seven plasmids and produces a bacteriocin.…”
Section: Resultsmentioning
confidence: 81%